Theoretical Design of a Multilayer Based Spectrally Selective Solar Absorber Applied Under Ambient Conditions - Shi, Kuang; Liu, Huaiyu; Wang, Lei; Bie, Yu; Yang, Yue (Frontiers in Energy Research, 2021)
With the increasing of global energy requirements and environmental problems, the use of solar thermal energy has attracted widespread attention. The selective solar absorption coating is the most important part of a solar thermal conversion device. At present, most of the coatings work well in a vacuum at a high temperature, while not stably in the air environment. Based on the high-temperature resistant and infrared-reflective properties of ITO, a multilayer film of SiO2/Si3N4/SiO2/ITO/Cr has been designed as a selective solar absorber. The genetic algorithm is applied to optimize the material and thickness selection for each layer. The results show that the optimized multilayer film could achieve a high solar absorptance up to 90% while keeping a relatively low infrared emittance around 50% for temperature change between 600 ℃ and 900 ℃. All the materials composing this film have been tested before to be chemically stable at a high temperature up to 900 ℃ in the air environment. It is also adaptive to different incident angles from 0° to 60°. The finite-difference time-domain method was also adopted to plot the energy density distribution for different wavelengths, which provided the underlying mechanism for the selective emission spectrum. The findings in this study would provide valuable guidance to design a low-cost selective solar absorption coating without the need for vacuum generation.